Knowledge Among General Population of Rawalpindi, about Crimean-Congo Haemorrhagic Fever (CCHF) - Tariq Masood Khan , Nadeem Ikram (Journal of Rawalpindi Medical College, 2018)
Background: To find out the awareness about Crimean-Congo Hemorrhagic Fever (CCHF) among residents of Rawalpindi Methods: In this descriptive cross sectional survey, participants from general population of Rawalpindi were included. The sample size for the study consisted of 300 individuals. The data was collected using a self structured pre tested questionnaire and was analyzed using SPSS 21. Results: Majority of the participants in the study were males (79%). Regarding their educational status 55.7% were illiterate and almost 63% had heard previously regarding it and claimed to be having information regarding CCHF. Their sources of information were variable but the majority (25.3 %) got it through sources like friends, colleagues, warning posters, brochures etc. according to the people who were aware, 19.7% viewed its transmission from infected person and almost same number stated it to be transmitted by animal source, almost 13.3% labeled it as airborne, while 11% thought its transmission through ticks. Conclusion: CCHF is a life threatening disease and has more chances to become prevalent in Pakistan . A meticulous multidisciplinary effort is required to manage the situation. Due to poor infrastructure, lack of education and limited access to health-related and livestock-related facilities, preventive measures are rare. The general population of rural and urban areas should have awareness about the signs and symptoms, mode of spread and seriousness of the disease.